Rationale simplified hardening training and recreational complexes future teachers - Verbludov I.B; Loza T.А (Kharkov National Pedagogical University, 2010)
Distribution in the modern world epidemiological diseases are influenza and acute respiratory viral infections requires a search for simplified, effective preventive means. The main direction of prevention of these diseases is to strengthen and enhance the activities of the immune system. Strengthening the protective systems of the body is directly related to the constant holding of different types of hardening. This study illustrates the possibility of using quenching air and water in the independent exercise training and recreational facilities in all conditions of students.